2017
DOI: 10.1158/1078-0432.ccr-17-0146
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of KPC1 Ubiquitin Ligase Affects the NF-κB Pathway in Melanoma

Abstract: Purpose Abnormal activation of the NF-κB pathway induces a more aggressive phenotype of cutaneous melanoma. Understanding the mechanisms involved in melanoma NF-κB activation may identify novel targets for this pathway. KPC1, an E3 ubiquitin ligase, is a regulator of NF-κB pathway. The objective of this study was to investigate the mechanisms regulating KPC1 expression and its clinical impact in melanoma. Experimental Design The clinical impact of KPC1 expression and its epigenetic regulation were assessed i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 48 publications
4
45
0
Order By: Relevance
“…Incorrect regulation of NF-κB has been linked to cancer, inflammatory and autoimmune diseases. Studies showed that novel epigenetic regulation of KPC1 associated with NF-κB pathway activation, promoting metastatic melanoma progression ( 24 ). These results suggest that it is possible for the steroid 9(11)-DHEP affect melanoma progression via its potential immunosuppressive effect by inhibiting the NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Incorrect regulation of NF-κB has been linked to cancer, inflammatory and autoimmune diseases. Studies showed that novel epigenetic regulation of KPC1 associated with NF-κB pathway activation, promoting metastatic melanoma progression ( 24 ). These results suggest that it is possible for the steroid 9(11)-DHEP affect melanoma progression via its potential immunosuppressive effect by inhibiting the NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…RNA isolation from FFPE was performed as previously described (19). Briefly, deparaffinization was performed using standard xylene and ethanol rinse, and then digested by proteinase K. RNA was extracted using RNA-Solv Reagent (Omega Bio-Tek) with chloroform, followed by overnight precipitation in isopropanol and the addition of Pellet Paint NF (Novagen).…”
Section: Dna and Rna Isolationmentioning
confidence: 99%
“…The ubiquitin-proteasome system (UPS) plays critical functions to maintain cellular homeostasis. As such the UPS controls the turnover of vital proteins that function in diverse processes such as the cell cycle, DNA-damage repair, cell metabolism, and cell stress [8][9][10][11]. The UPS controls a myriad of cell signaling pathways involved in the cell's inflammatory response, growth, migration, invasion, and homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…NF-κB1 (p105) and NF-κB2 (p100) are normally processed and activated into p50 and p52, respectively, by the proteasome system [16]. NF-κB1, or p105, is ubiquitinated by the ubiquitin-E3 ligase KIP1 ubiquitination-promoting complex subunit 1 (KPC1, also called RNF123 for ring finger protein 123) [9]. Ubiquitinated NF-κB1 is processed in the proteasome, which results in the formation and accumulation of p50 in different tumor types [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation